Gestão da qualidade e do desenvolvimento de produtos nos arranjos produtivos locais de confecções do Paraná - Monteiro, Antonio Roberto Giriboni (Universidade Federal de São Carlos, 2008)
Due to the need to improve business competitiveness and create jobs, has seen in the last decade, the emergence of Brazil Local Clusters (APLs), following a trend seen in other countries, mainly in Italy. These arrangements are characterized by similar productive and high degree of interaction between companies. In Paraná were identified 22 APLs, seven of which are linked to the textile sector, this sector which is responsible for the second largest generation of jobs in the state. Considering the importance of APLs and the textile sector for the Paraná, this work was aimed at reviewing the major general practice of quality management and the development of products made by companies in local productive arrangements. He had specific goals as the characterization and comparison of APLs on quality management and development of products and identifies the actions of the government or local governance that can contribute to the development of APLs. To achieve the goals was conducted through a search of seven case studies APLs in the textile sector of Paraná. The main outcome was possible identify a heterogeneity in the treatment of quality management and the development of products in APLs of the state and in general where there is investment in quality management and the development of products there is a strengthening of the companies that are becoming, this so, less susceptible to external competition.
Keywords: Gestão da qualidade; Desenvolvimento de produtos; Arranjo organizacional; Indústria têxtil; ENGENHARIAS::ENGENHARIA DE PRODUCAO